1991
DOI: 10.1007/bf00341385
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic leaks in colorectal cancer surgery: a risk factor for recurrence?

Abstract: This study examines anastomotic leaks as a potential influence on the long term outcome of patients with colorectal cancer. 167 patients were studied who had clinical and radiological assessment of anastomotic integrity in the post-operative period, following potentially curative resections for left-sided colonic or rectal cancer. There was no evidence of a leak in 135 of these patients, while the remaining 32 developed a clinical and/or a radiological leak. At the end of a mean follow-up of 25 months, 15 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
2
6

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 15 publications
4
81
2
6
Order By: Relevance
“…In größeren Studien waren Anastomosenkomplikationen in 3-66% für einen letalen Krankheitsverlauf verantwortlich [4,20,23,26], zusätzlich wurden sie für eine erhöhte Rate am Tumorrezidiven [2] und schlechte funktionelle Ergebnisse verantwortlich gemacht [24]. Die Angaben über die Häufigkeit des Auftretens von Anastomoseninsuffizienzen variieren in Abhän-gigkeit von ihrer Lokalisation [26].…”
unclassified
“…In größeren Studien waren Anastomosenkomplikationen in 3-66% für einen letalen Krankheitsverlauf verantwortlich [4,20,23,26], zusätzlich wurden sie für eine erhöhte Rate am Tumorrezidiven [2] und schlechte funktionelle Ergebnisse verantwortlich gemacht [24]. Die Angaben über die Häufigkeit des Auftretens von Anastomoseninsuffizienzen variieren in Abhän-gigkeit von ihrer Lokalisation [26].…”
unclassified
“…The septic consequences of anastomotic failure are associated with significant mortality and morbidity rates [9], with reported mortality rates varying between 6 and 22% [10]. In addition, it has been shown that anastomotic failure increases the recurrence rates and decreases tumour-free survival rates [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Fewer reoperations for postoperative bleeding or leakage may be expected as well, thus reducing the hospital stay. Increased recurrence of malignancy is seen after leakage of colorectal anastomosis, which has been attributed to spill of tumor cells through the anastomotic site [60,61,62,63]. If the incidence of leakage can be reduced as a result of staple line reinforcement, it seems likely that there would be a positive effect on tumor recurrence as well.…”
Section: Discussionmentioning
confidence: 99%